Decentralized Infrastructure for Digital Notarizing, Signing, and Sharing Documents Securely Using Microservices and Blockchain - Irimia Cosmin-Iulian; Iftene Adrian (IEEE Access)
This paper introduces a microservice-based architecture to revolutionize how official documents are shared, verified, and stored in digital formats. Addressing the pressing issues of privacy, security, and trust, the proposed solution enables the partial and full sharing of documents while safeguarding sensitive data. The architecture comprises seven core microservices, including a data extractor, document obfuscator, notarization service, and decentralized storage through blockchain and IPFS. By obfuscating designated document fields and utilizing a distributed ledger for notarization, the system ensures both the privacy of users and the transparency required for official verification. Through the combination of state-of-the-art encryption techniques, video-based notarization, and blockchain for immutability, this approach enables secure, scalable, and privacy-conscious document sharing. Detailed guidelines are provided for each microservice, from data extraction and field obfuscation to notarization and decentralized storage. Our approach resolves common issues such as data tampering, unauthorized access, and identity fraud while offering a framework for future innovations in digital notarization.